Photoconductivity of An Inorganic /Organic Composites Containing Dye-Sensitized (Zinc Oxide) - Kareem, Aseel A.; Jaffer, Harith I.; Al-Lamy, Hussein K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we study the effect of adding Zinc Oxide powder (ZnO) at different ratios (10%,20%,30%,40%,50%) as particles and organic dyes rhodamine B(RhB), rohdamine 6G(Rh6G) and eosin(EO) are added at different doping ratios to polystyrene (PS), to form photosensitized(PS/ZnO/dye) composites, for samples were prepared as films by spin method. Photoconductive properties are investigated.     For I-V characteristic measurements, the photocurrent (Iph) and dark current (Id) are generally increased in non linear behavior with increasing light intensity and applied voltage for all composites. The photocurrent goes decrease through its maximum value at high white light intensities or high voltage for 2.4*10-5mol/l RhB/A composites where A=0.06g PS+0.18g ZnO, while the dark current remains nearly constant.